Diseño de secuencias peptídicas derivadas de la lectina de arachis hypogaea para el reconocimiento del antígeno Tn (2020)
Cancer diagnostic methods are currently based on glycosylated biomarkers such as Tn antigen and can be detected by lectin-based technologies such as biosensors. However, there is a limitation due to the lack of commercial availability of lectins that recognize these structures, in addition to the fact that low stability may occur in biosensors due to the layers of proteins associated with them. In the present work we analyzed peanut lectin (Arachis Hypogaea), together with other lectins from legumes belonging to the Fabaceae family such as Glycine max (PDB 4D69), Wisteria Floribunda (PDB 5KXB), Psophocarpus Tetragonolobus (PDB 2D3S), and Isolectin B4 Vicia Villosa (1N47); where, based on their characteristics, peptides were designed and modeled and analyzed by means of molecular docking tests. Twelve candidate peptides were obtained for the library, eleven of which come from the structural segmentation of our protein of interest Arachis Hypogaea and one obtained from the comparisons and alignments of all the fabaceous proteins. The peptides analyzed by molecular docking were considered stable, of adequate length, with energy properties similar to peanut lectin when coupled with the antigen Tn, being considered excellent candidates to be later synthesized and analyzed for possible cancer diagnostic methods.